STUDI KEBIJAKAN PENDIDIKAN : MAKNA, URGENSI DAN RELEVANSINYA BAGI PENGEMBANGAN PENDIDIKAN ISLAM - Khabibul Khoiri; M. Agus Kurniawan (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
Thoughts on the development of Islamic education to encourage critical analytical thinking, creative and normative in the face of various practices and current issues in the field of education weeks to be studied and analyzed from fondasionalnnya dimensions so as not to lose the spirit or the spirit of Islam and / fragility philosophical foundation, as well as the face of the trend. Emphasis on the importance of students to live by the values of goodness, spirituality and morality as neglected. In fact the opposite is happening. Nowadays, many educational institutions have been transformed into industrial business, which has a pragmatic vision and mission. Education geared to deliver pragmatic individuals who work to achieve material success and social professions that will prosperity themselves, companies and countries. In secular Western culture, a person's high education does not correspond to the goodness and happiness of the individual concerned. The impact of the hegemony of Western education on Muslims is that many Muslims have a high education, but in real life, they have not become good and happy Muslims. There is still a gap between the high degree of education achieved and the low morals and morals of Muslim life. This is due to the pragmatic vision and mission of education. Actually, Islam has a more comprehensive and integrative goal than the secular education system which solely produces students who have a pragmatic paradigm.